PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE DALAM PEMBELAJARAN MENCERITAKAN KEMBALI ISI TEKS BIOGRAFI DENGAN MEDIA CETAK - Pipit Dewi Puspitasari; Sarwiji Suwandi; Raheni Suhita (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This study aims to describe the quality of the learning process and the skills of retelling the contents of the biographical text with the print media using the Think Talk Write model of learning in students of class X Motorcycle Technique (TSM) B SMK Gamaliel 1 Madiun. This study is a Classroom Action Research (PTK) which is implemented in two cycles, with each cycle consisting of four stages, namely planning, action, observation, and reflection. Subjects in this study were students of class X TSM B consisting of 21 male students. Data collection techniques used in this study include observation, field notes, interviews, documentation, and ability tests. This research used compative descriptive data anlysis technique. The results showed that the application of Think Talk Writelearning model with print media can improve the quality of the learning process and the skills of retelling the content of the biography of the students in cycle I and cycle II. This is indicated by the improvement of process quality from cycle I with an average score of 71,42 increased in cycle II with an average score of 90,47. Then, skill enhancement retells the contents of the biography text in cycle I with an average score of 70,42 increases in cycle II with an average score of 82,80.